The impact of the decline of marine spoils in the tax policy of the Eyalet of Algeria - boualem, seffah (The Algerian Historical Journal, 2026)
This study aims to show the effect of the decline in the activity of the marine spoils in imposing a new strike policy for the Eilat of Algeria, where the marine revenues from material and human spoils developed and increased in the financial revenues resulting from them, and they generated huge amounts of money for the state treasury, and the marine spoils witnessed different stages in the revenues from the period For another, from the stage of ascension during the sixth and seventeenth centuries to the stage of stagnation and contraction at the end of the seventeenth century AD, which prompted the authority to follow a tax policy in order to compensate for the shortfall resulting from the decline in revenues from maritime activity, as taxes were imposed on Christian countries sailing in the Mediterranean, and the volume of taxes increased. on the Algerian population.